Italian Art and English Artists in the English Quattrocento: Naturally Seeking Out Things Italian - Kennedy, Kathleen Erin (The sixteenth century journal, 2023)
Rather than resist humanism and Renaissance art styles, fifteenth-century English illuminators engaged the humanist art style known as bianchi girari and developed their own Anglo-Italian versions. They were the only non-Italian artists in Europe to do so. Extant examples suggest that Tito Livio Frulovisi introduced Cristoforo Cortese's bianchi girari initials to England when he arrived in Duke Humphrey of Gloucester's household in 1436. English artists immediately began adapting this style, and subsequent generations of artists continued to develop it through the 1470s. The artists known as the Caesar Master and Followers of the Corpus Master also invented English approaches to bianchi girari that persisted into later decades. Thus, English manuscripts demonstrate sustained interest in Renaissance art, and notably Venetian art, among English artists and patrons for fifty years before the Tudor period.